Offering vegetables to children at breakfast time in nursery and kindergarten settings: the Veggie Brek feasibility and acceptability cluster randomised controlled trial - Chris J. McLeod; Emma Haycraft; Amanda J. Daley (BMC, 2023)
Abstract Background In many Westernised countries, children do not consume a sufficient amount of vegetables for optimal health and development. Child-feeding guidelines have been produced to address this, but often only promote offering vegetables at midday/evening meals and snack times. With guidance having limited success in increasing children's vegetable intake at a population level, novel approaches to address this must be developed. Offering vegetables to children at breakfast time in nursery/kindergarten settings has the potential to increase children's overall daily vegetable consumption as children typically attend nursery/kindergarten and many routinely eat breakfast there. However, the feasibility and acceptability of this intervention (Veggie Brek) to children and nursery staff has not been investigated. Methods A feasibility and acceptability cluster randomised controlled trial (RCT) was undertaken in eight UK nurseries. All nurseries engaged in one-week baseline and follow-up phases before and after an intervention/control period. Staff in intervention nurseries offered three raw carrot batons and three cucumber sticks alongside children's main breakfast food each day for three weeks. Control nurseries offered children their usual breakfast. Feasibility was assessed by recruitment data and nursery staff's ability to follow the trial protocol. Acceptability was assessed by children's willingness to eat the vegetables at breakfast time. All primary outcomes were assessed against traffic-light progression criteria. Staff preference for collecting data via photographs versus using paper was also assessed. Further views about the intervention were obtained through semi-structured interviews with nursery staff. Results The recruitment of parents/caregivers willing to provide consent for eligible children was acceptable at 67.8% (within the amber stop-go criterion) with 351 children taking part across eight nurseries. Both the feasibility and acceptability of the intervention to nursery staff and the willingness of children to consume the vegetables met the green stop-go criteria, with children eating some part of the vegetables in 62.4% (745/1194) of instances where vegetables were offered. Additionally, staff preferred reporting data using paper compared to taking photographs. Conclusions Offering vegetables to children at breakfast time in nursery/kindergarten settings is feasible and acceptable to children and nursery staff. A full intervention evaluation should be explored via a definitive RCT. Trial registration NCT05217550.